2020
DOI: 10.3390/polym12081678
|View full text |Cite
|
Sign up to set email alerts
|

Micellization Behaviour of Linear and Nonlinear Block Copolymers Based on Poly(n-hexyl isocyanate) in Selective Solvents

Abstract: Block copolymers have attracted significant scientific and economic interest over the last decades due to their ability to self-assemble into ordered structures both in bulk and in selective solvents. In this work, the self-assembly behaviour of both linear (diblocks, triblocks and pentablocks) and nonlinear (miktoarm stars and a block-graft) copolymers based on poly(n-hexyl isocyanate), PHIC, were studied in selective solvents such as n-heptane and n-dodecane. A variety of experimental techniques, namely stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The higher percentage of LC block in the structure, the higher tendency of the copolymer to form an anisotropic phase. 22,[25][26][27][28][29][30]32,39,50,54 The phase transition of the solution is a function of two parameters of temperature and concentration. The orientation change of LC molecules as a function of free energy and temperature was discussed by Guo et al 55 The effect of solution concentration (0.2, 0.4, and 0.6 mg/mL in toluene) and temperature (25-100°C) on the LC texture of samples was investigated.…”
Section: Dsc Analysis Of P 1 P 2 and P 3 Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher percentage of LC block in the structure, the higher tendency of the copolymer to form an anisotropic phase. 22,[25][26][27][28][29][30]32,39,50,54 The phase transition of the solution is a function of two parameters of temperature and concentration. The orientation change of LC molecules as a function of free energy and temperature was discussed by Guo et al 55 The effect of solution concentration (0.2, 0.4, and 0.6 mg/mL in toluene) and temperature (25-100°C) on the LC texture of samples was investigated.…”
Section: Dsc Analysis Of P 1 P 2 and P 3 Samplesmentioning
confidence: 99%
“…Recently, poly (n-hexyl isocyanate) (PHIC) and its copolymers have attracted considerable attention because of their potential applications and unique properties in areas such as chiral recognitions, optical switches, liquid crystals, degradable materials, nanocomposites, blend of polymers, electrical devices, biomaterials, nanowires, thermoreversible gels, and activators. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] These copolymers are so important that various behaviors of linear and nonlinear block copolymers based on PHIC have been investigated by Vazaios et al 32 The known methods used for copolymerization of PHIC are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they may behave either as rigid rods or as semiflexible worm-like chains. Combination of PICs with other rigid or more flexible chains in diblock copolymers or more complex macromolecular architectures opens new horizons in nanotechnology focusing on the microphase separation, the ordering kinetics and the self-assembly behavior in solution [9][10][11]. Consequently, novel applications are expected to emerge, making these materials possible candidates as optical switches, recognition devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric surfactants are now used to control the emulsion rheology and applied in various industries like oil recovery [ 1 , 2 ], cosmetics [ 3 ] and drug delivery [ 4 ]. Generally, the stability of emulsion limits its application.…”
Section: Introductionmentioning
confidence: 99%